CITRA SOSIAL PEREMPUAN DALAM CERPEN KARTINI KARYA PUTU WIJAYA TINJAUAN KRITIK SASTRA FEMINIS - Diana, Jumianti (Jurnal Pena Indonesia, 2018)
The character of Ami in Kartini short story describe as couregeous and smart woman. Ami with the bravery tell her speech about Kartini in the Kartini Days in front of female regent and other ladies. Ami regard as herself and other women in Indonesia as that continues women fight like Cut Nyak Dhien and Sagung Wah. Ami hopes Indonesia women more brave to fight their right autority and brave to take their decision to improve themselves. The social character of Amy as the smart woman just look by the way to analyze and tell about the Kartini desired through Amis speech into the short story can express about differences between emancipation and feminism.